2016
DOI: 10.1021/acs.jpclett.6b02221
|View full text |Cite
|
Sign up to set email alerts
|

Helium Diffraction as a Probe of Structure and Proton Order on Model Ice Surfaces

Abstract: Helium diffraction has the potential to reveal the degree of proton order at an ice surface, and has been used in the past to benchmark theoretical work. We demonstrate that previous calculations do not represent the diffraction experiment to a sufficient degree of accuracy. By combining a realistic helium-water potential with quantum calculations using exact close-coupling methods we demonstrate that the scattering is strongly energy dependent. Proton order may be inferred best from selective adsorption reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…For example, on graphene, water has previously only been visualised when subsurface, due to its dynamic nature 61,62 . Compared with other techniques, He atom scattering has the advantage of being the most delicate surface-probing technique and is sensitive to H atoms in the top layer [63][64][65][66] . All measurements have therefore been performed using the Cambridge helium-3 spin-echo facility (HeSE) 27,67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, on graphene, water has previously only been visualised when subsurface, due to its dynamic nature 61,62 . Compared with other techniques, He atom scattering has the advantage of being the most delicate surface-probing technique and is sensitive to H atoms in the top layer [63][64][65][66] . All measurements have therefore been performed using the Cambridge helium-3 spin-echo facility (HeSE) 27,67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…The first set of data was obtained from sum frequency experiments on the surface of ice, which showed orientational disordering of surface water molecules at 200 K 17 that was first interpreted as a proxy for premelting and later confirmed in another independent study 60 . The second set of data was obtained from helium scattering studies 61 that previously could not help discern whether the basal surface of ice showed ordered arrangements of protons, such as Fletcher's phase 38 , or a disordered arrangement in which the Fletcher phase is not dominant, as it was suggested by more recent measurements 62 . Buch used dynamical and Monte Carlo simulations based on TIP4P-ice 63 to show that the Fletcher striped phase of protons was most stable and in fact this arrangement was found to be stable until surface reconstruction occurs above 180 K. Comparison of the models with previous sum frequency generation (SFG) studies 64,23 provided additional evidence to support the hypothesis that protons adopt ordered arrangements at the surface.…”
Section: [H1] High Vacuum and Modelling Studiesmentioning
confidence: 99%
“…Due to the large cross section of HAS to isolated adsorbates (including hydrogen as described in Section 3.5), the position and structure of hydrogen atoms and adsorbed water layers can be readily determined. [103][104][105] These include also the hydrogenation of a graphene surface 106 while H-positions are hard to determine with other methods (e.g., hydrogen is a weak scatterer for electrons) which also present a severe risk of damaging the H-layer. 107 In a study of highly proton-ordered water structures on oxygen pre-covered Ru(0001) it could be shown that the atomic oxygen and the oxygen from water form a (2 Â 2) surface reconstruction, which however, is broken by the hydrogen to give a (2 Â 4) surface reconstruction: while LEED measured a (2 Â 2), HAS measured a (2 Â 4) superstructure.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%